Evaluation of the Antimicrobial Efficacy of a Novel Rifampin/Minocycline-Coated, Noncrosslinked Porcine Acellular Dermal Matrix Compared With Uncoated Scaffolds for Soft Tissue Repair. (October 2016) - Majumder, Arnab; Scott, Jeffrey R.; Novitsky, Yuri W.
Background . Despite meticulous aseptic technique and systemic antibiotics, bacterial colonization of mesh remains a critical issue in hernia repair. A novel minocycline/rifampin tyrosine–coated, noncrosslinked porcine acellular dermal matrix (XenMatrix AB) was developed to protect the device from microbial colonization for up to 7 days. The objective of this study was to evaluate the in vitro and in vivo antimicrobial efficacy of this device against clinically isolated methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli. Methods . XenMatrix AB was compared with 5 existing uncoated soft tissue repair devices using in vitro methods of zone of inhibition (ZOI) and scanning electron microscopy (SEM) at 24 hours following inoculation with MRSA or E coli . These devices were also evaluated at 7 days following dorsal implantation and inoculation with MRSA or E coli (60 male New Zealand white rabbits, n = 10 per group) for viable colony-forming units (CFU), abscess formation and histopathologic response, respectively. Results . In vitro studies demonstrated a median ZOI of 36 mm for MRSA and 16 mm for E coli for XenMatrix AB, while all uncoated devices showed no inhibition of bacterial growth (0 mm). SEM also demonstrated no visual evidence of MRSA or E coli colonization on the surface of XenMatrix AB compared with colonization of all other uncoated devices. In vivo XenMatrix AB demonstrated complete inhibition of bacterial colonization, no abscess formation, and a reduced inflammatory response compared with uncoated devices. Conclusion . We demonstrated that XenMatrix AB possesses potent in vitro and in vivo antimicrobial efficacy against clinically isolated MRSA and E coli compared with uncoated devices.